Vision and flexibility in a model of cognitive dissonance - Junichiro Ishida (Osaka University, Institute of Social and Economic Research (ISER), 2010)
This paper explores the consequences of cognitive dissonance, coupled with timeinconsistent preferences, in an intertemporal decision problem with two distinct goals: acting decisively on early information (vision) and adjusting flexibly to late information (flexibility). The decision maker considered here is capable of manipulating information to serve her self-interests, but a tradeoff between distorted beliefs and distorted actions constrains the extent of information manipulation. Building on this tradeoff, the present model provides a unified framework to account for the conformity bias (excessive reliance on precedents) and the confirmatory bias (excessive attachment to initial perceptions).
Keywords: D03; D99; 330; Cognitive dissonance; Vision; Flexibility; Conformity bias; Confirmatory bias; Kognition; Zeitpräferenz; Entscheidungstheorie